Preparing a Generation Ready for Work: The Role of Internal Locus of Control and Future Orientation in Vocational School Students - Tsuraya Nuha Afifah; Pratista Arya Satwika (Universitas Katolik Soegijapranata, 2025)
Vocational High Schools (SMK) function as educational institutions designed to equip students with practical skills to enter the workforce directly, making them more prepared to face professional challenges. However, reality shows that there are still many unemployed people who come from SMK graduates, students still doubt their abilities, and do not have a clear future direction, which shows a lack of work readiness. This study aims to examine the relationship between internal locus of control and future orientation with work readiness in SMK students. A quantitative approach with multiple linear regression analysis was employed, involving 100 students from class XI a public vocational high school in Surakarta through simple random sampling. The research instruments included the Work Readiness Scale, the Internal Locus of Control Scale, and the Future Orientation Scale. The results revealed a significant relationship between internal locus of control and future orientation with career readiness, both simultaneously and partially.